Nonlinear parameter of heart rate variability can diagnose early cardiac autonomic neuropathy. Issue 3 (18th March 2020) - Dubey, Pramita; Verma, Manish; John, Nitin Ashok; Gutch, Manish
Abstract: This is a case of a 63‐year‐old female presenting with diabetes mellitus, hypertension, hypothyroidism, and postmenopausal osteoporosis with findings showing abnormal AFT with reduced heart rate variability (HRV) and multiple lobed Poincaré plot, pointing to premature atrial contractions. Abstract : This is a case of a 63‐year‐old female presenting with diabetes mellitus, hypertension, hypothyroidism, and postmenopausal osteoporosis with findings showing abnormal AFT with reduced heart rate variability (HRV) and multiple lobed Poincaré plot, pointing to premature atrial contractions.